2022
DOI: 10.3390/horticulturae8070612
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Technologies of Fresh Citrus Fruit: Advances and Recent Developments for the Loss Reduction during Handling and Storage

Abstract: Citrus spp. are spread mainly in the Mediterranean basin and represent the largest fruit source for human consumption. Postharvest losses, mainly due to diseases and metabolic disorders of fruits, can cause severe wastage, reaching 30 to 50% of the total production. Preserving quality and extending shelf life are essential objectives for postharvest technological innovation, determined by the proper handling, treatment, storage and transport of harvested produce. Moreover, the application of novel sustainable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 259 publications
(305 reference statements)
1
13
0
Order By: Relevance
“…Each of these factors can have a positive, negative, or neutral effect on the weight loss process. These results are in agreement with the observations of Strano et al 60 , who reported that storage duration plays a crucial role in citrus fruit weight reduction, which is primarily due to moisture loss. In addition, Motamedi et al 61 reported significant differences in fruit weight reduction during storage among different citrus species.…”
Section: Discussionsupporting
confidence: 93%
“…Each of these factors can have a positive, negative, or neutral effect on the weight loss process. These results are in agreement with the observations of Strano et al 60 , who reported that storage duration plays a crucial role in citrus fruit weight reduction, which is primarily due to moisture loss. In addition, Motamedi et al 61 reported significant differences in fruit weight reduction during storage among different citrus species.…”
Section: Discussionsupporting
confidence: 93%
“…In tropical regions, postharvest losses in citrus fruits pose a significant challenge due to their rapid deterioration during handling, storage, and transport ( Strano et al, 2022 ). Lemons, being non-climacteric fruits, emit low levels of CO 2 and ethylene during postharvest storage that led to moderate softening or compositional alterations during storage and transport.…”
Section: Introductionmentioning
confidence: 99%
“…Citrus fruits in general are susceptible to infections of fungal pathogens, such as species of Alternaria , Colletotrichum , Geotrichum , and Penicillium [ 10 , 11 , 12 , 13 ], which are responsible for both pre- and post-harvest rots. The most common and serious post-harvest types of rot of citrus fruits are green and blue molds caused by Penicillium digitatum and P. italicum , respectively, followed by sour rot caused by Geotrichum citri-aurantii [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%